A GEO, SOCIO-ECONOMIC ANALYSIS OF SLUMS IN GRATER VISAKHAPATNAM - Marapatla, Gangayya (IJRDO - Journal of Social Science and Humanities Research, 2017)
Rapid population growth, industrialization and urbanization in the country are adversely affecting the environment. Though the relationship is complex, population size and growth tend to expand and accelerate these human impacts on the environment. All these in turn lead to an increase in the pollution levels. However, environmental pollution not only leads to deteriorating environmental conditions but also have adverse effects on the health of people. India is one of the most degraded environment countries in the world and it is paying heavy health and economic price for it. Various agencies, especially those in developing countries are finding it difficult to respond to this situation effectively. Greater Visakhapatnam, a significant port city on the east coast of Peninsular India, strategically located midway between Kolkata and Chennai, is one of the fastest developing cities in Southeast Asia. This strategic geographical location coupled with the availability of the other associated factors of logistics has enabled the city to attract large commercial investments and the major public and private sectors’ industries. In recent years, there has been a spurt in investments in the city and its surrounding areas giving further impetus to transform the city as a future mega city.